Quality evaluation of squid processed by ultra-high pressure based on fuzzy mathematic method - HU Qinglan; YU Haixia; YANG Shuibing; REN Xiying; DONG Kaicheng; YANG Zhijian; HU Yaqin (浙江大学学报. 农业与生命科学版, 2013)
Squid (Dosidicus gigas) has become one of important aquatic protein resources nowadays because of its appetizing, nourishing quality, low price as well as large fishing amount. However, because of its high insoluble myostromin (11.0%) and connective tissue with longitudinal, radial and circular orientations in squid muscle, its meat was sensitive to heat processing which made the traditional squid product taste tough and hard, as a result hindering greatly the edibility of old people and infant. Until now, the methods of activating endogenous protease or adding exogenous enzymes were usually used for improving the quality of squid meat, while the enzymic method would damage its appearance and was harmful for maintaining the quality. Ultra-high pressure technology is one kind of physical technology with high efficiency. Previous studies had found that ultrahigh pressure technology could improve the quality of meat.This study aims to evaluate the quality of squid meat processed by ultra-high pressure based on fuzzy mathematic method and to find out the optimal ultra-high pressure processing conditions. Based on weight analysis of sensory evaluation about the color, texture, flavor and taste of treated squid slice by ultra-high pressure processing, a sensory rating system was established. An overall rating by fuzzy mathematics comprehensive evaluation method was also made on the pressure, the processing time, and the temperature of ultra-high pressure. At the same time, the texture and color of squid slice treated by ultra-high pressure were also investigated to verify the feasibility and accuracy of fuzzy mathematics comprehensive evaluation method.The results showed that the quality weight collection of squid slice was K=(color 0.25, texture 0.15, flavor 0.35, taste 0.25), and the sensory quality appeared to be the best when the squid slice was treated by 300 MPa at 25℃ for 10 min by fuzzy mathematics comprehensive evaluation method. Meanwhile, the texture and whiteness of treated sample by instrument measurement were influenced in descending order as follows: pressure > temperature > time, and the optimal condition was 300 MPa at 25℃ for 10 min, which was correspondence with the result of fuzzy mathematics sensory evaluation. Under this optimal condition, the squid meat was with the best elasticity, the lowest shear force, and the optimal sensory quality.It is concluded that the ultra-high pressure treatment can improve the quality of squid meat, and it is further confirmed the feasibility and accuracy of the fuzzy mathematics sensory evaluation and instrumental analysis.